2001
DOI: 10.1212/wnl.57.3.430
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexplained death in children with epilepsy

Abstract: This case series represents the largest series of sudden unexplained death in children with epilepsy. At least two previously described risk factors for SUDEP in adults, low serum AED levels at time of death and AED polytherapy, do not appear to be significant in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
148
5
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 169 publications
(159 citation statements)
references
References 20 publications
3
148
5
3
Order By: Relevance
“…W większo-ści przypadków dochodzi do tego w nocy lub podczas snu, bez świadków zdarzenia [650]. Największym czynnikiem ryzyka SUDEP są częste drgawki, a zwłaszcza uogólnione drgawki toniczno-kloniczne [651][652][653][654][655][656][657][658][659][660].…”
Section: Nagły Niewyjaśniony Zgon W Przebiegu Padaczkiunclassified
“…W większo-ści przypadków dochodzi do tego w nocy lub podczas snu, bez świadków zdarzenia [650]. Największym czynnikiem ryzyka SUDEP są częste drgawki, a zwłaszcza uogólnione drgawki toniczno-kloniczne [651][652][653][654][655][656][657][658][659][660].…”
Section: Nagły Niewyjaśniony Zgon W Przebiegu Padaczkiunclassified
“…Over the years, further refinements to knowledge of SUDEP incidence have been made. Briefly, it has been reported that SUDEP is responsible for up to 17% of all deaths in epilepsy 33 with an incidence rate among adults between 1:500 and 1:1,000 patient-years while in children SUDEP varies on average 2/10.000 patient-years 33,34 . WHY?…”
Section: Sudden Cardiac Death In Epilepsy Disappoints But Epileptolomentioning
confidence: 99%
“…The majority of deaths are unwitnessed; most series report only 10 to 20% witnessed cases, making it difficult to ascertain whether a seizure precedes death (19)(20)(21)(22). When witnessed and unwitnessed cases are considered, 50 to 90% of cases have evidence of a convulsive seizure before death (14,(19)(20)(21)(22)(23)(24) Sudden death is over 20 times more frequent in people with epilepsy than the general population. The literature on clinical risk factors is now able to define individuals at the highest risk.…”
Section: Circumstances Of Deathmentioning
confidence: 99%